2003
DOI: 10.1073/pnas.0307042101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hippocampal noradrenaline and serotonin release in galanin-overexpressing mice after repeated forced swimming test

Abstract: Basal and forced swimming (FS) stress-induced release of noradrenaline (NA) and serotonin (5-HT) were determined by in vivo microdialysis in the ventral hippocampus of mice overexpressing galanin under the platelet-derived growth factor B promoter (GalOE͞P) or under the dopamine ␤-hydroxylase promoter (GalOE͞D) (only NA). WT mice served as controls. Intraventricular infusion of galanin significantly reduced basal extracellular NA in WT mice and in GalOE͞P mice (albeit less so). Microdialysis sampling during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Under basal conditions, galanin has been shown to reduce LC neuronal activity (Pieribone et al, 1995) and NA release (see above), probably via stimulation of the GalR1(R3) receptors (Ma et al, 2001). Under stressful conditions, galanin would probably increase the stress-reactivity of the LC NA system (Yoshitake et al, 2004;Kuteeva et al, 2005) and/or exert a direct postsynaptic effect in the LC projection areas, further contributing to depression-like behavioral changes (Weiss et al, 1998(Weiss et al, , 2005.…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depresmentioning
confidence: 99%
See 1 more Smart Citation
“…Under basal conditions, galanin has been shown to reduce LC neuronal activity (Pieribone et al, 1995) and NA release (see above), probably via stimulation of the GalR1(R3) receptors (Ma et al, 2001). Under stressful conditions, galanin would probably increase the stress-reactivity of the LC NA system (Yoshitake et al, 2004;Kuteeva et al, 2005) and/or exert a direct postsynaptic effect in the LC projection areas, further contributing to depression-like behavioral changes (Weiss et al, 1998(Weiss et al, , 2005.…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depresmentioning
confidence: 99%
“…A number of behavioral studies suggested a potential role of galanin in depression-like behavior in rodents (see Fuxe et al, 1998;Weiss et al, 1998Weiss et al, , 2005Yoshitake et al, 2004;Kuteeva et al, 2005Kuteeva et al, , 2007Lu et al, 2005aLu et al, , 2007Swanson et al, 2005;Barr et al, 2006;Karlsson and Holmes, 2006;Ö gren et al, 2006). Bilateral infusion of galanin into the ventral tegmental area (VTA) (Weiss et al, 1998), or intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
“…A large literature also demonstrates that extracellular fluid concentrations (ECF) of serotonin are increased in both the vicinity of the DRN and the corticolimbic targets of the serotonin system, including the mPFC, amygdala and hippocampus. The stressors shown to cause this increase in ECF, which is almost certainly due to increased serotonin release, range from exposure to a predator, tail pinch, elevated platform exposure, inescapable shock, social defeat, to restraint/immobilization (Adell et al, 1997;Amat et al, 2001;Bland et al, 2003;Funada and Hara, 2001;Grahn et al, 1999;Hajos-Korcsok et al, 2003;Jordan et al, 1994;Kang et al, 2005;Kawahara et al, 1993;Keck et al, 2005;Keeney et al, 2006;Kehr et al, 2001;Kirby et al, 1995Kirby et al, , 1997Kirby and Lucki, 1998;Maswood et al, 1998;Miyata et al, 2007;Mokler et al, 2007;Petty et al, 1994;Price et al, 2002;Renard et al, 2003;Rex et al, 2005;Rueter and Jacobs, 1996;Storey et al, 2006;Takahashi et al, 2000;Thorre et al, 1997;Yoshioka et al, 1995;Yoshitake et al, 2004). It is important to note however that not all studies have found increases in forebrain ECF serotonin in response to stress and there are actually some reports of stress-induced decreases (e.g., Kirby et al, 1997;Rueter and Jacobs, 1996).…”
Section: Serotonin Releasementioning
confidence: 99%
“…route or into the dopaminergic ventral tegmental area induced depression-like behavior in the rat forced swim test (FST) (5,6). Several studies in GAL-overexpressing transgenic mice reported an increased depression-like behavior in the FST (7,8) but found no differences in anxiety-related behavior under baseline conditions (7,9). Holmes et al (9) suggested, however, that GAL might have protective effects during periods of elevated stress, because GAL overexpression counteracted anxiogenic effects evoked by noradrenergic stimulation.…”
mentioning
confidence: 99%